2016
DOI: 10.1038/ncomms11067
|View full text |Cite
|
Sign up to set email alerts
|

Splicing misregulation of SCN5A contributes to cardiac-conduction delay and heart arrhythmia in myotonic dystrophy

Abstract: Myotonic dystrophy (DM) is caused by the expression of mutant RNAs containing expanded CUG repeats that sequester muscleblind-like (MBNL) proteins, leading to alternative splicing changes. Cardiac alterations, characterized by conduction delays and arrhythmia, are the second most common cause of death in DM. Using RNA sequencing, here we identify novel splicing alterations in DM heart samples, including a switch from adult exon 6B towards fetal exon 6A in the cardiac sodium channel, SCN5A. We find that MBNL1 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
158
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(174 citation statements)
references
References 73 publications
(123 reference statements)
14
158
1
1
Order By: Relevance
“…To verify factors that may change the regulation of sodium current, we chose to analyze the expression level of the Na V 1.5 (Scn5a) protein by immunoblotting. Previously, the mis‐splicing of SCN5A without affecting mRNA level has been reported in a DM patient study . Our normalized Western blot results showed no significant changes of Na V 1.5 protein level between WT and DM mutant mice, which is compatible with the results seen in patients (Figure ; n=4 in each group, P =0.564).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…To verify factors that may change the regulation of sodium current, we chose to analyze the expression level of the Na V 1.5 (Scn5a) protein by immunoblotting. Previously, the mis‐splicing of SCN5A without affecting mRNA level has been reported in a DM patient study . Our normalized Western blot results showed no significant changes of Na V 1.5 protein level between WT and DM mutant mice, which is compatible with the results seen in patients (Figure ; n=4 in each group, P =0.564).…”
Section: Resultssupporting
confidence: 91%
“…In a study by Freyermuth et al, 23 inclusion of the exon 6A of SCN5A (the gene that encodes Na V 1.5 sodium channel) was increased in DM heart samples as well as in Mbnl1 KO; Mbnl2 HET mice. Through a series of electrophysiological analysis on different isoforms they concluded that the misregulation of SCN5A splicing accounts for DM arrhythmia . In concordance with this report, Wahbi et al also reported that Brugada syndrome may cause cardiac sudden death in DM patients and SCN5a mis‐splicing may play a role.…”
Section: Discussionsupporting
confidence: 64%
“…Although the physiological significance of AS regulation of trafficking and membrane-dynamics-related processes is an underexplored area, previous work definitely hints at its importance. For example, recently, AS misregulation of the sodium channel SCN5A has been shown to contribute to cardiac conduction delay and arrhythmia in mice, similarly to what is observed in myotonic dystrophy (Freyermuth et al, 2016). Previously, mis-AS of Bin1 in mice has been associated with T-tubule alterations and skeletal muscle weakness, predominant features of myotonic dystrophy (Fugier et al, 2011).…”
Section: Discussionmentioning
confidence: 81%
“…Several abnormal splicing events have been identified in heart samples of DM1 patients, and recently, it has been shown that missplicing of SCN5A, the gene encoding the cardiac sodium channel, contributes to conduction system disease and arrhythmias in this disease. 21 Moreover, it also is important to keep in mind that the CTG expansion is unstable at the somatic level and tends to increase in different tissues, including the heart, (2) 4 (2) 2 (1) 3 (1) 8 (4) LV dysfunction 75 (9) 16 (7) 16 (8) 17 (8) 26 (12) Values are numbers (%) of observations or median (quartile). LV indicates left ventricular, SVA, supraventricular arrhythmia; and VTA, ventricular tachyarrhythmias.…”
Section: Personal Medical Historymentioning
confidence: 99%